1991
DOI: 10.11150/kansenshogakuzasshi1970.65.1200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluconazole on Aspergillus Infection Associated with Chronic Granulomatous Disease

Abstract: Aspergillus infection is the most frequent fungal infection associated with chronic granulomatous disease (CGD), and often results in a life-threatening situation. This report describes the use of high-dose fluconazole, a new antifungal agent, for invasive Aspergillus infection in a patient with CGD. A 27-month-old boy was sent to our hospital because of unknown fever in October, 1988. He was then admitted for pneumonia and pleural effusion of the right lung in February, 1989. Treatment with antibiotics was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on these findings, it would be tempting to suggest a possible role for fluconazole in disseminated aspergillosis, either as prophylaxis in patients at risk, or in early disseminated lesions, but the available clinical evidence has to be carefully assessed. Administration of fluconazole (250 mg day −1 ) resulted in clinical and radiological improvement in aspergillosis complicating chronic granulomatous disease, where treatment with miconazole, flucytosine and amphotericin B had been ineffective 48 . Similarly, Mizuguchi et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on these findings, it would be tempting to suggest a possible role for fluconazole in disseminated aspergillosis, either as prophylaxis in patients at risk, or in early disseminated lesions, but the available clinical evidence has to be carefully assessed. Administration of fluconazole (250 mg day −1 ) resulted in clinical and radiological improvement in aspergillosis complicating chronic granulomatous disease, where treatment with miconazole, flucytosine and amphotericin B had been ineffective 48 . Similarly, Mizuguchi et al.…”
Section: Discussionmentioning
confidence: 97%
“…Administration of fluconazole (250 mg day )1 ) resulted in clinical and radiological improvement in aspergillosis complicating chronic granulomatous disease, where treatment with miconazole, flucytosine and amphotericin B had been ineffective. 48 Similarly, Mizuguchi et al 49 found fluconazole to be effective in therapy of a patient with semi-invasive aspergillosis, while van Burik et al 28 described a patient with cutaneous aspergillosis in whom no new lesions developed while the patient was receiving fluconazole (200 mg day )1 ). In contrast, Kujath and Lerch 50 reported that Aspergillus infections of multiple soft tissue injuries did not improve with fluconazole therapy.…”
Section: Discussionmentioning
confidence: 99%